Smart nanocarrier-based chitosan @silica coated carbon nanotubes composite for breast cancer treatment approach. Issue 12 (13th August 2022) - El-Shahawy, Ahmed A. G.; Elnagar, Noha; Zohery, Medhat; Abd Elhafeez, Maha Sabry; El-Dek, S. I.
Abstract: The nonspecificity of doxorubicin (DOX), as well as its oral bioavailability, is a major obstacle in the clinical setting. This study was based on the change of pH value and designed for the 1st time a novel nano-matrix; multiwall carbon nanotubes (MWCNTs) coated with mesoporous silica (MS) and chitosan (CS). The latter possessed a unique nanostructure with pH-sensitivity in DOX release to be administered orally for the treatment of breast cancer. The loaded DOX and entrapment efficiency reached 64% and 99%, respectively. The results of MWCNTs@MS@CS@DOX confirmed its efficiency as pH-based drug delivery for oral breast cancer therapy. Graphical Abstract: UF0001